Planejamento baseado em locais em atividades e locais com características de não repetitividade - Slobodzian, Jocemar; Granja, Ariovaldo Denis (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Construction planning can be classified into two categories, an activity-based (ABP) or a location-based (LBP). The ABP includes traditional planning methods, such as the Critical Path Method (CPM). LBP has many benefits when applied to high repetition constructions. The objective of this paper is to verify whether the procedures of LBP, already consolidated for repetitive constructions, apply in a non-repetitive work structure and what benefits are obtained when compared to ABP. A case study is conducted in a common area of a commercial building in Brazil, which was originally scheduled using ABP planning methods and compared with LBP. The results show that it is possible to apply the procedures related to LBP in non-repetitive construction, assuring the flow of work and resources.